Extraction and Partial Characterization of Lectin from Indonesian Brown Algae Padina australis and Padina minor - Nurrahmi Dewi Fajarningsih; Naomi Intaqta; Danar Praseptiangga; Choiroel Anam (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2019)
Extraction and partial characterization of lectin from Indonesian Padina australis and Padina minor had been carried out. The crude extract of the P. australis and P. minor were examined for hemagglutination activity (HA) using native and trypsin-treated of rabbit and human A, B, O type erythrocytes. Both extracts agglutinated all of the trypsin-treated erythrocytes tested in the HA assay. Strong HA was detected in the crude extract of P. minor with trypsin-treated of human type A and O erythrocytes. However, the sugar-binding specificity study through the quantitative hemagglutination inhibition (HI) assay showed that P. minor extract could not specifically recognize the glycans tested. Apparently, the HA of the P. minor was more due to its co-extracted polyphenols content than its lectin content. On the other hand, the HI assay showed that asialo transferrin human (aTf) and asialo porcine thyroglobulin (aPTG) were the most powerful in inhibiting the HA of P. australis. Those indicated that P. australis protein extract was able to specifically recognized aTf and aPTG. The stability of P. australis and P. minor HA over various temperatures, pH ranges, and divalent cations studies showed that the P. minor HA was stable on a wide range of pH and temperature; not affected by the presence of EDTA, but decreased by Ca2+ and Mg2+ additions showed that P. minor protein extract  was not a metallic protein. The HA of P. australis decreased at 60 oC and was inactivated at 90 oC; increased at strong acidic (pH 3 4) and strong basic (pH 9 10) and dependent by the presence of either EDTA or Ca2+ and Mg2+ divalent cation.